The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1016/s0730-725x(01)00399-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of slice orientation on reproducibility of fMRI motor activation at 3 Tesla

Abstract: The effect of slice orientation on reproducibility and sensitivity of 3T fMRI activation using a motor task has been investigated in six normal volunteers. Four slice orientations were used; axial, oblique axial, coronal and sagittal. We applied analysis of variance (ANOVA) to suprathreshold voxel statistics to quantify variability in activation between orientations and between subjects. We also assessed signal detection accuracy in voxels across the whole brain by using a finite mixture model to fit receiver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…Slice-orientation, as reported by Gustard et al (2001), had a non-significant impact on the reproducibility of the fMRI signal when isotropic voxels and a simple motor paradigm were used. Spatial normalisation was shown to have a significant effect on the reproducibility of visual activation by some (Swallow et al, 2003), but not others (Miki et al, 2000).…”
Section: Introductionmentioning
confidence: 89%
“…Slice-orientation, as reported by Gustard et al (2001), had a non-significant impact on the reproducibility of the fMRI signal when isotropic voxels and a simple motor paradigm were used. Spatial normalisation was shown to have a significant effect on the reproducibility of visual activation by some (Swallow et al, 2003), but not others (Miki et al, 2000).…”
Section: Introductionmentioning
confidence: 89%
“…data (Gustard et al, 2001). This model overcomes the binormal assumption of the classical parametric methods and can be generalised to any statistical score (Genovese, Noll, & Eddy, 1997); it is directly applicable in our context using either the t or the F SPMs.…”
Section: Structural Image the Image Is In Neurological Convention (Lmentioning
confidence: 97%
“…The algorithm provides us with the mixing proportion (the estimated proportion of activated voxels) and effect size which best fit the data. These were estimated using a maximum likelihood procedure (Gustard et al, 2001).…”
Section: Structural Image the Image Is In Neurological Convention (Lmentioning
confidence: 99%
“…The optimization of slice orientation in fMRI studies has not received a lot of attention in the literature, although one study has suggested that oblique axial slices yield the best signal detection accuracy for a motor cortex experiment and coronal slices yield the worst (Gustard et al, 2001). The spatial dimensions of the human brain in the Talairach atlas (Talairach and Tournoux, 1988) (omitting the cerebellum) are 105 mm (I/S), 165 mm (A/P), and 123 mm (R/ L).…”
Section: Introductionmentioning
confidence: 99%